Spatial mapping of soil erosion prediction through integration USLE model into Geography Information System - Yusuf, Sri Malahayati; Murtilaksono, Kukuh; Lawaswati, Dwi Mei (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
The application of USLE model to several watersheds in Indonesia shows the diversity of processes that affect soil erosion. The integration of USLE model into Geography Information System (GIS) is able to provide a spatial distribution of soil erosion classes. This study aims to predict the soil erosion rate in various land cover in Ciesek sub watershed by integrating the USLE model into GIS. Undisturbed and disturbed soil sampling was carried out based on soil map unit, accompanied by observations of soil physic characteristics. Soil erosion prediction was done using the raster calculator with input raster-based data that has a certain spatial resolution. Analysis of the erosion class distribution on various land cover and slope classes was carried out by using the cross tabulation method. The results showed that the very low soil erosion class was dominant in the study location, namely in areas with forest land cover. The highest predicted of soil erosion rate resulted from bare land, followed by moorland and mix garden.